Remo BODEI, Roberto ESPÓSÍTO, F. MARTINEZ MARZOA, J.L. VILLACAÑAS; Manuel CRUZ (comp.): Los filósofos y la política. - López Cruchet, Julián (Anales del Seminario de Historia de la Filosofía, 2000)
Sin resumen